Pendidikan profesi guru untuk meningkatkan mutu pendidikan - Syamsidah Lubis (Inovasi Kurikulum, 2020)
The purpose of writing this article is to know the process of Professional Teacher Education (PPG) in Indonesia. Teacher Professional Education Program (PPG) is educational program organized to prepare S1 graduate of education and S1 / D IV non-educated who have talent and interest to be master the competence of teachers as a whole in accordance with national standard of education. The method in writing this article is Library Studies. Library Studies is an activity to collect information relevant to the topic or problem that becomes the object of research. Such information can be obtained from books, scientific papers, theses, dissertations, encyclopedias, internet, and other sources. In improving the quality of education, one of the programs that has been made is Teacher Professional Education Program (PPG), with the Professional Teacher Education (PPG) will improve the quality of teachers and improve the quality of education.   Abstrak Tujuan dari penyusunan artikel ini adalah untuk memahami proses perjalanan Pendidikan Profesi Guru (PPG) di Indonesia. Program Pendidikan Profesi Guru (PPG) ialah tata olah pendidikan yang dilaksanakan untuk mempersiapkan lulusan S1 kependidikan dan S1/Diploma IV nonkependidikan yang mempunyai minat dan bakat untuk menjadi guru agar menguasai kapabilitas guru secara menyeluruh setakar dengan standar nasional pendidikan. Adapun metode pada penulisan artikel ini adalah studi pustaka. Aktivitas untuk mengumpulkan informasi yang signifikan dengan masalah atau topik yang menjadi objek penelitian merupakan pengertian dari studi pustaka. Informasi yang tercantum dapat ditemukan mulai dari buku-buku, ensiklopedia, disertasi, tesis, karya ilmiah, internet, dan sumber-sumber lainnya. Dalam meningkatkan mutu pendidikan, salah satu program yang telah dibuat adalah program Pendidikan Profesi Guru (PPG), melalui adanya Pendidikan Profesi Guru (PPG) akan meningkatkan kualitas guru dan meningkatkan mutu pendidikan. Kata kunci: Pendidikan Profesi Guru (PPG); Mutu Pendidikan